ACUTE IZONIAZID POISONING WITH PRESENTATION OF A CLINICAL CASE - Evgenia Barzashka; Vasil Atanasov; Teodora Valova; Olimpiada Atmazhova (Peytchinski Publishing, 2022)
Rimicid or isonide a group of medications which belong to anti-tuberculosis medicaments. The active substance isoniazid is used to treat pulmonary and extrapulmonary forms of tuberculosis, as well as prophylaxis in case of contact with infected individuals. Isoniazid is rapidly absorbed, reaching a maximum serum concentration in 2 hours, and penetrates all body fluids. The volume of distribution is approximately 0.6 l/kg. Isoniazid causes pyridoxine deficiency in two ways: - by hydrazones, isoniazid metabolites inhibit the pyridoxal kinase, which converts pyridoxine to the active form, pyridoxal-5-phosphate, and - pyridoxine deficiency disrupts the synthesis and metabolism of GABA, the main inhibitory mediator of the central nervous system. Isonicotinic acid poisoning metabolism is subject to individualized factors, and in some people, this metabolism can be in a significantly slower. A clinical case of poisoning with 30 tablets of Rimicid by a 16-year-old girl suicidal attempt was presented. The results of the TC analysis confirm intoxication with the drug, and the retrospective assessment of the concentration over a past period of time using the elimination half-life has revealed an extremely high dose of ingested isoniazid.